POTENSI FEMALE ATHLETE TRIAD PADA ATLET REMAJA PUTRI DEFISIENSI BESI - Fillah Fithra Dieny; Deny Yudi Fitranti; Firdananda Fikri Jauharany; A Fahmy Arif Tsani (PERSATUAN AHLI GIZI INDONESIA, 2021)
The female athlete triad (FAT) is a syndrome that occurs in female athletes who have a combination of 3 related conditions and are associated with sports. The aimed of this study to analyze the relationship between iron deficiency and the state of the female athlete triad (FAT) in female athletes. The design of this study was cross sectional with 80 subjects of female athletes aged 12-18 years from various sports, who were taken by simple random sampling. The research was conducted at the Central Java Student Center for Education and Sports Training (BPPLOP). Bivariate analysis was performed using the Spearman test. Based on Ferritin, as many as 15 subjects (18.25%) had iron deficiency anemia, and FAT syndrome was not found in the subjects, however, when each sign was seen, 20 percent were classified as polimenorrhea and oligomenorrhea, and 37.5 percent experienced eating disorders. There were a significant relationship between iron deficiency based on serum ferritin (p = 0.015; r = 0.273) and Hb levels (p = 0.002; r = 0.337) with the component of athlete's bone density. However, iron deficiency (based on serum Ferritin and Hb levels) did not show a significant association with menstrual cycle disorders and eating disorders (p 0.05). Female Athlete Triad has not been found among subjects, but athletes have experienced eating behavior disorders, menstrual cycle disorders and the risk of low bone density. Iron deficiency is associated with decreased bone density in young female athletes. ABSTRAK Female athlete triad (FAT) merupakan suatu syndrom yang terjadi pada atlet wanita yang memiliki kombinasi dari 3 kondisi yang saling berkaitan, dan berhubungan dengan olahraga. Tujuan penelitian untuk menganalisis hubungan defisiensi besi dengan keadaan female athelete triad (FAT) pada atlet remaja putri. Desain penelitian ini adalah cross-sectional dengan 80 subjek atlet putri berusia 12-18 tahun dari berbagai cabang olahraga yang diambil secara simple random sampling. Penelitian dilakukan di Balai Pemusatan Pendidikan dan Latihan Olahraga Pelajar (BPPLOP) Jateng. Analisis univariat untuk mendeskripsikan data berupa distribusi dan persentase. Analisis bivariat dilakukan menggunakan uji Spearman. Berdasarkan data serum ferritin, sebanyak 15 subjek (18,25%) mengalami anemia defisiensi besi, namun belum ditemukan kejadian FAT pada subjek, tetapi bila dilihat masing masing tanda sebanyak 20 persen tergolong polimenorea dan oligomenorea, serta 37,5 persen mengalami gangguan perilaku makan. Ada hubungan yang signifikan antara defisiensi besi berdasarkan serum ferritin (p=0,015; r=0,273) dan kadar Hb (p=0,002; r=0,337) dengan komponen kepadatan tulang atlet. Namun defisiensi besi (bedasarkan serum Ferritin dan Kadar Hb) tidak menunjukkan hubungan yang signifikan dengan gangguan siklus menstruasi dan gangguan perilaku makan (p0,05). FAT belum ditemukan pada atlet remaja putri, namun atlet sudah ada yang mengalami gangguan perilaku makan, gangguan siklus menstruasi dan risiko kepadatan tulang rendah. Defisiensi besi berhubungan dengan menurunnya kepadatan tulang atlet remaja putri.Kata kunci: atlet; remaja putri; defisiensi besi; female athlete triad (FAT)